Design Thinking para inovação em turismo de experiência no complexo turístico Itaipu - Junior, Vilson Poltronieri (2022)
Innovation is a critical factor for the development of organizations and is strongly associated with economic growth. Regardless of the field of activity, it must be seen as a source of differentiation and competitive advantage. Therefore, it is necessary to constantly seek tools and approaches that contribute to a culture of innovation. In the segment of services linked to the tourism industry, the current scenario suggests changes to the conventional practices of offering the tourist product, in response to a new mode of consumption, which is based on living experiences capable of re-signifying individuals, and which can be analyzed from the concepts of the experience economy, proposed by Pine & Gilmore (1999). At the Itaipu Tourist Complex (CTI), the offer of incredible, planned and sustainable tourist experiences is the goal of its quality policy, and it seeks this guarantee through processes and methods that promote innovation. As the experience is unique to each individual, the proposal of formatting a tourist product must be centered on the individual and take into account all the points of contact he has with the service consumed. Given this context, an approach that has gained prominence for its nature focused on the human being, for its collaborative and integrative characteristic, and for its proposal to contribute in an innovative way in solving complex problems is Design Thinking. Given this context, this research aimed to apply and evaluate the results and contributions of Design Thinking as a method for innovation projects in experience tourism at the CTI. In order to achieve the proposed objectives, the research method presents a qualitative approach of an exploratory nature, with the application of field research and is classified as a case study, in which the object of investigation was the Itaipu Tourist Complex. In addition to bibliographic and documental research and a systematic literature review, the instruments for collecting and interpreting data also had the practical application of the seven stages of Design Thinking, for which a working group with eight employees was set up. The practical intervention of the research in the organization took place between August 2020 and November 2021, and resulted in the ideation of 51 opportunities, contributed to the development of a collaborative work culture, enabled the elaboration of an overview of the experiences offered, the elaboration of a short-term improvement plan and the development of a new tour, entitled Itaipu By Bike. Finally, Design Thinking proved to be a practical method that was well accepted by the team for the development of projects focused on the formatting of tourist experiences in the Itaipu Tourist Complex, which will be adopted for future projects both for the creation of new products and services and for in-depth information gathering.